HIV and Tuberculosis co-infection impacts T-cell activation markers but not the numbers subset of regulatory T-cells in HIV-1 infected patients - Moustapha Mbow; Ndèye S.S. Santos; Makhtar Camara; Awa Ba; Aliou Niang; Géraldine Daneau; Djibril Wade; Abdou A. Diallo; Maxim Toupane; Maïmouna Diakhaté; Nafissatou Lèye; Papa A. Diaw; et al. (AOSIS, 2013)
Background: Tuberculosis (TB) has been shown to accelerate the clinical course of HIV infection, but the mechanisms by which this occurs are not well understood. Regulatory T-cells (Tregs)are known to dampen hyperactivation of the immune cells, but it remains unclear whether hyperactivation of T-cells in HIV infection is associated with a decrease of Tregs and what the effect Mycobacterium tuberculosis (MTB) co-infection has on T-cell activation and Tregs. Objectives: In this study, we aim to evaluate whether active TB is associated with the increased expression of T-cell activation markers and reduced number of Treg cells in HIV-1-infected patients. Methods: This study was conducted on 69 subjects consisting of 20 HIV-infected patients,20 HIV and MTB co-infected patients, 19 MTB-infected patients and 10 uninfected control subjects negative for both MTB and HIV. The frequencies of T-cell activation markers (CD38 and HLA-DR) and Treg cells (CD4+CD25+CD127-) were measured by flow cytometry. Results: Significantly higher expression of CD38 and HLA-DR on CD4+ and CD8+ T-cells was found in MTB and HIV co-infected patients compared with HIV-infected patients. However,no significant difference in the percentage of Treg cells was reported between HIV patients with TB and those without. The study also showed a negative correlation between regulatoryT-cells frequency and CD4+ T-cell counts. Conclusion: These results suggest that TB enhances the expression of peripheral T-cell activation markers during HIV infection, whilst having no impact on the percentages of Tregcells.